THE SHAM OF SPATIAL FREEDOM IN LABOR AT THE AGROHIDRONEGOCIO OF SUGARCANE IN THE EDR OF ARACATUBA-SP - Cardoso, Messias Alessandro [UNESP] (Univ Estadual Paulista Julio Mesquita Filho, Fac Ciencias & Tecnologia, 2016)
At this paper, the efforts converged to the attempt of developing some critical thinking about the territorial labor mobility that the workmen from Maranhao and Alagoas are submitted at the agrohidronegocio of sugarcane in the EDR of Aracatuba-SP. In this sense, the capital system uses as territorial asset, the process of territorial labor mobility, aiming the use of labor in the territories that are more profitable to the capital. This use is enabled by the labor mobility, which is in the origin of added value production, and thus, capital accumulation.
Keywords: Labor territorial mobility Labor; Spatial freedom